MENUMBUHKAN KESADARAN PENTINGNYA PENGUASAAN BAHASA INGGRIS - Desriani Nggolaon; Sitti Hardianti; Nurhaida Lakuana (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
The ability to communicate in English has become an important key in the current era of globalization. This study aims to explain the urgency and plans for community service activities carried out at SMP N 1 Buko, Banggai Islands Regency, with a focus on improving students' mastery of English. Based on observations, there are still many students who face difficulties in basic skills such as reading, writing, listening and speaking in English. This activity is designed to increase awareness of the importance of English and improve students' skills in four aspects of the language. The methods used include coordination with schools, observation, preparation and implementation of programs involving various practical and interactive activities. It is hoped that the results of this activity can make a positive contribution in overcoming the gap between students' English language mastery needs and their actual abilities, so that they are better prepared to face future challenges.